2019
DOI: 10.1021/jacs.9b00082
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanocrystal Etching as a Means of Probing the Dynamic Chemical Environment in Graphene Liquid Cell Electron Microscopy

Abstract: Graphene liquid cell electron microscopy has the necessary temporal and spatial resolution to enable the in situ observation of nanoscale dynamics in solution. However, the chemistry of the solution in the liquid cell during imaging is as yet poorly understood due to the generation of a complex mixture of radiolysis products by the electron beam. In this work, the etching trajectories of nanocrystals were used as a probe to determine the effect of the electron beam dose rate and preloaded etchant, FeCl 3 , on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 77 publications
3
115
0
Order By: Relevance
“…Compared with the microchip cell, the graphene cell can normally achieve better resolution due to less scattering from the window material and smaller liquid thicknesses. In addition, it does not require an expensive dedicated sample holder [51][52][53][54][55]. However, this technique is currently limited in several ways.…”
Section: Different Tem Configurations For Imaging Liquid Samplesmentioning
confidence: 99%
“…Compared with the microchip cell, the graphene cell can normally achieve better resolution due to less scattering from the window material and smaller liquid thicknesses. In addition, it does not require an expensive dedicated sample holder [51][52][53][54][55]. However, this technique is currently limited in several ways.…”
Section: Different Tem Configurations For Imaging Liquid Samplesmentioning
confidence: 99%
“…[4][5][6][7][8] Therefore, understanding the atomicscale mechanisms of nanomaterial dissolution in liquid electrolyte is of primary importance to design more efficient nanotechnologies. In that regards, liquid cell transmission electron microscopy (LCTEM) has become a method of choice to observe the oxidative etching of individual nanostructures such as metallic nanoparticles [9][10][11][12][13][14][15][16][17] and nanoalloys [18][19][20][21] and it has provided a unique observation window on the intermediate nanostructures formed during these dynamic processes. Like the nucleation and growth of nanoparticles, 22,23 the dissolution mechanisms are simultaneously driven by kinetic and thermodynamic effects that depend on the reaction speed and the structural stability of nanomaterials, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, LCTEM allowed highlighting the effects of oxidation potential, nanoparticle faceting and crystal defects on selective-etching processes. [11][12][13]20 However, the influence of surface functionalization on the corrosion dynamics has always been disregarded, although the nature and spatial distribution of organic shells are known to affect the stability and reactivity of nanostructures. 4,6,24,25 From theoretical point of view, different approaches have been actively developed to understand the role of surfactants on the structure of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] Different from some previous studies, no effect of bubble was observed in the etching process because the ZnO nano/micro belts were covered by water completely due to its hydrophilicity (after O 2 plasma treatment). [ 18,42,43 ] The electron beam dose rate was kept the same (in the range of 40 e − (Å 2 ·s) −1 ) in the process of etching individual ZnO nano/micro belts except for that shown in Figure S4, Supporting Information. The ZnO nano/micro belts etching processes were recorded by a K2 camera (Gatan Inc, Pleasanton, CA, USA) with the exposure time of 0.5 s for each video frame.…”
Section: Methodsmentioning
confidence: 99%